The role of diet and supplementation in the prevention and treatment of autism spectrum disorders - Aleksandra Mazurek; Damian Machaj; Jakub Polak; Daniel Grobecki; Jakub Lis; Dominik Machaj; Przemysław Raczkiewicz; Weronika Adamik (Kazimierz Wielki University, 2023)
The role of diet and supplementation in the prevention and treatment of autism spectrum disorders There is evidence indicating the positive effects of dietary intervention in the prevention and treatment of autism spectrum disorders. There are studies linking maternal vitamin D deficiency with ASD in offspring. Children and adolescents on the autism spectrum are also supposed to have significantly lower concentrations of vitamin D than healthy children and adolescents. This indicates the role of vitamin D supplementation in the prevention and treatment of ASD(5). Diets most commonly used in the therapy of autism spectrum disorders are: dairy-free and gluten-free, specific carbohydrate diet, low phenol, low oxalate and ketogenic diet(4). The most popular of them are dairy-free and gluten-free. However, studies conducted by Dr. James Adams attribute the highest effectiveness to a diet of specific carbohydrates(7). After applying the ketogenic diet, improvements in concentration, learning ability and social behavior were observed(1,26). However, it should be remembered that the scientific literature contains a small number of reliably conducted studies confirming the effectiveness of individual diets and supplementation in the prevention and treatment of ASD. Therefore, the positive impact of dietary intervention is still referred to as "potential". In addition, the use of certain diets may be associated with side effects, such as vomiting and hypoglycemia in the case of a ketogenic diet (1,28) and underweight in the case of elimination diets(16). Therefore, the introduction of dietary changes for therapeutic purposes should be carried out under the constant supervision of doctors and dieticians.